Clinical Care Strategies That Support Parents of Children With Complex Chronic Conditions*. Issue 7 (5th April 2021) - Bogetz, Jori F.; Revette, Anna; DeCourcey, Danielle D.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Children with complex chronic conditions often receive inpatient and end-of-life care in the ICU, yet little is known about the clinical care strategies that best support this unique group of parents. This study aimed to elucidate supportive clinical care strategies identified by bereaved parents of children with complex chronic conditions. DESIGN: Qualitative analysis of 21 open-response items from the cross-sectional "Survey of Caring for Children with Complex Chronic Conditions" querying communication, decision-making, and end-of-life experiences. SETTING: Large tertiary care children's hospital. PATIENTS: Parents of children with complex chronic conditions who received care at a large academic institution and died between 2006 and 2015. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: An iterative multistage thematic analysis of responses was used to identify key themes pertaining to clinical care strategies that support parents of children with complex chronic conditions. Open-ended responses were analyzed from 110 of 114 (96%) of survey respondents. The majority of parents had children with congenital/chromosomal complex chronic conditions who died 3.9 years (interquartile range, 2.2–6.7 yr) prior to their parents' study participation. Although informational themes related to clear honest communication, consistent messaging, and enhanced care coordination were identified, parents emphasized the relational aspects of clinical care including inclusivity of their expertise about their child's needs, recognition of their unique experience as parents, and maintenance of connection with clinicians through bereavement. CONCLUSIONS: Clinical care strategies that support parents of children with complex chronic conditions reflect the unique needs of this group of children. Relational strategies such as including parents as experts in their child's care were paramount to parents of children with complex chronic conditions throughout their child's medical journey and at end of life.